The Languages of the Crisis: Pathographies in the Latest Serbian Literature - Nowak-Bajcar, Sylwia (Porównania, 2021)
The article presents selected works by Serbian prose writers (David Albahari, Svetislav Basara, Ɖorđe Pisarev, Igor Marojević, Vladimir Arsenijević) created in the last three decades, dealing with the problem of Serbia’s relations with Europe, including the issue of this country’s accession to the European Union. The interpretative key to the analysis of this problem is the category of disease, which is a metaphor for the crisis affecting not only Serbia, but—in the opinion of authors belonging to different generations—the whole world. The skepticism manifested in the works of the presented writers is not an expression of the authors’ personal attitude to the issue of Serbia’s integration with the European Union, but rather a sad reflection on their country’s unpreparedness for this process, resulting from the complex socio-political situation and difficult historical experiences that led to it.